(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Africa has gone through many economic, cultural and gender oriented problems throughout the history. Women in general are supressed and are made silent suffers of the laws and statutes made by the patriarchal society. In this patriarchal society, man is treated as the lord and on the other hand woman is treated as servant. The women are expected to fulfil the expectations of the male dominated culture. Women who undergo the patriarchal nuisances of the society try to overcome them by finding different ways. They try to come out of the pit of patriarchy by expressing their pent- up feelings and emotions. Black women are not an exception to this and they too express themselves by writing. Buchi Emecheta belongs to the Igbo community, so she highlights the difficulty of the women of the Igbo culture. This paper briefly discusses the blues and the woes of the women of the Igbo polygamous society with reference to Buchi Emecheta’s The Joys of Motherhood. The novel portrays the sufferings of the protagonist, Nnu Ego. She suffers along with her nine children at the age of forty fulfilling the Igbo cultural expectations.